Desenvolvimento de bebida láctea potencialmente probiótica carbonatada: características físico-químicas, microbiológicas e sensoriais - Jardim, Fernanda Barbosa Borges; Santos, Elisa Norberto Ferreira; Rossi, Daise Aparecida; Melo, Roberta Torres de; Miguel, Daniela Peres; Rossi, Elizeu Antônio; Sylos, Celia Maria de [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The goal of this work was to develop a strawberry fl avored dairy beverages carbonated and fermented with potential probiotic bacteria. Four formulations of dairy beverages were elaborated: Control (BL); Fermented (BLF); Carbonated (BLC) and Carbonated Fermented (BLFC). In samples submitted for carbonation, a carbonator was used for the carbon dioxide (CO2 ) gas injection dissolved in drinking water and the cultivation consisting of lactic bacteria Lactobacillus acidophilusLA-5®, Bifi dobacterium BB-12® and Streptococcus thermophilus (Biorich, Chr. Hansen) was employed on the fermented samples. The samples were characterized by physical and chemical, microbiological and sensory parameters. The BLC sample showed the presence of yeasts and coliform counts, but the counts indicated that it was suitable for consumption in 28 days time. The BL presented average coliform counts above the limit established by the law after 21 days of refrigerated storage. The presence of lactic bacteria and CO2 and their effects on lower proteolysis indexes, lower pH values and higher acidity values were correlated with signifi cant inhibitory effect of contaminated microorganisms in the BLF and BLFC. The carbonation was not stimulatory for the growth of lactic crops, mainly in the genus Bifi dobacterium spp. and Streptococcus spp. The BLF drink presented greater sensory acceptance and purchase intention test results, however the carbonated beverage presented positive results, with mean values greater than 50% in the acceptance tests with potential inclusion as sensory differential in dairy beverages. Just BLFC drink was considered potentially probiotic, by presenting minimum counts of Lactobacillus spp. during storage. Further studies should be conducted with the technology of carbonation, since it has been proven the correlation of the presence of CO2 with inhibitory effect of contaminated microorganisms and lower physical and chemical changes of dairy beverages.

O objetivo deste trabalho foi desenvolver uma bebida láctea sabor morango carbonatada e fermentada com bactérias potencialmente probióticas. Foram elaboradas quatro formulações de bebida láctea: Controle (BL); Fermentada (BLF); Carbonatada (BLC) e Fermentada Carbonatada (BLFC). Nas amostras submetidas à carbonatação, utilizou-se um carbonatador para injeção do gás dióxido de carbono (CO2 ) dissolvido em água potável e nas amostras fermentadas, adotou-se o cultivo Lactobacillus acidophilus-LA-5®, Bifi dobacterium BB-12® e Streptococcus thermophilus (Biorich, Chr. Hansen). As amostras foram caracterizadas quanto a parâmetros físico-químicos, microbiológicos e sensoriais. A BLC apresentou leveduras e coliformes totais, mas as contagens indicaram que estava própria para o consumo no tempo 28 dias. A BL apresentou contagens médias de coliformes totais acima do limite estabelecido pela legislação após 21 dias de estocagem refrigerada. A presença das bactérias lácticas e CO2 exerceram efeitos em menores índices de proteólise, menores valores de pH e maiores valores de acidez e estiveram correlacionados com o efeito inibitório de micro-organismos contaminantes nas BLF e BLFC. A BLF apresentou melhores resultados nos testes sensoriais de aceitação e intenção de compra, mas as bebidas carbonatadas apresentaram resultados positivos, com médias superiores a 50% nos testes de aceitação com potencial inserção como diferencial em bebidas lácteas. Apenas a bebida BLFC foi considerada potencialmente probiótica, por apresentar contagens mínimas de Lactobacillus spp. durante o armazenamento. Novos estudos devem ser conduzidos com a tecnologia de carbonatação, uma vez que houve correlação da presença de CO2 com efeito inibitório de deteriorantes e menores alterações físico-químicas nas bebidas lácteas.
Development of potential probiotic carbonated dairy beverages: physico-chemical, microbiological and sensory characteristics
Keywords: Fermented beverage; Carbonation; Microbiology; Proteolysis; Sensorial evaluation; Bebida carbonatada; Bactérias Láticas; Microbiologia; Proteólise; Avaliação sensorial